(untitled) - Hadi, Tenku Idris Tenku (Petaling Jaya, Selangor Darul Ehsan, Malaysia, 1996)
This boo reviews the general pattern of economic development in Malaysia from 1950 to 1955 as a backdrop to the overall study. Regional disparities and income niequalities have been identified as the fundamental issues necessitating an more intence pace of develoment in Malaysia.
Keywords: Đảo Langkawi (Kedah),Langkawi Island (Kedah); Điều kiện kinh tế,Economic conditions